ANALISIS INTEGRASI PLTB PADA STABILITAS FREKUENSI DALAM JARINGAN KELISTRIKAN SULBAGSEL BERDASARKAN RATE OF CHANGE OF FREQUENCY - Saputra, Rizky Wahyu Adi; Nugroho, Dedi (Elektrika, 2024)
The South Sulawesi electrical system, which is an interconnected network supplying electricity to South Sulawesi, West Sulawesi, Central Sulawesi, and Southeast Sulawesi, faces new challenges in integrating wind power plants (PLTB) into frequency stability. This study analyzes the impact of integrating wind power plants (PLTB) on the frequency stability of the Sulbagsel electrical system, focusing on the rate of change of frequency (RoCoF). Under normal conditions without PLTB, the system frequency remains stable at 50 Hz during both daytime and nighttime peak loads. Integration of PLTB causes the frequency to increase from 50 Hz to a maximum peak, ranging from 50.111 Hz to 50.978 Hz during the day and from 50.113 Hz to 50.613 Hz at night. A frequency decrease occurs when the PLTB is removed, with the frequency dropping from 50 Hz to a minimum value between 49.270 Hz and 49.884 Hz during the day and between 49.326 Hz and 49.884 Hz at night. These frequency fluctuations indicate the system's sensitivity to power variability from wind energy and the chal-lenges in managing frequency drops due to the loss of PLTB. The system response varies during peak load periods in the day and night, with smaller frequency fluctuations during the day compared to nighttime, possibly due to differences in load demand profiles and generator composition. These findings provide insights into the impact of PLTB on frequency stability and power management in renewable energy-based electrical systems. Keywords: WPP Integration, Frequency Stability, Rate of Change of Frequency (RoCoF).ABSTRAKSistem kelistrikan Sulawesi Selatan, yang merupakan jaringan interkoneksi yang memasok energi listrik ke Sulawesi Se-latan, Sulawesi Barat, Sulawesi Tengah, dan Sulawesi Tenggara, menghadapi tantangan baru dalam integrasi pembang-kit listrik tenaga bayu (PLTB) terhadap stabilitas frekuensi. Penelitian ini menganalisis dampak integrasi pembangkit listrik tenaga bayu (PLTB) terhadap stabilitas frekuensi sistem kelistrikan Sulbagsel, dengan fokus pada rate of change of frequency (RoCoF). Dalam kondisi normal tanpa PLTB, frekuensi sistem tetap stabil pada 50 Hz baik pada beban puncak siang maupun malam. Integrasi PLTB menyebabkan frekuensi meningkat dari 50 Hz hingga puncak maksimum, yaitu anta-ra 50,111 Hz hingga 50,978 Hz pada siang hari, dan antara 50,113 Hz hingga 50,613 Hz pada malam hari. Penurunan frekuensi terjadi ketika PLTB dihilangkan, dengan frekuensi turun dari 50 Hz ke nilai minimum antara 49,270 Hz hingga 49,884 Hz pada siang hari, dan antara 49,326 Hz hingga 49,884 Hz pada malam hari. Fluktuasi frekuensi menunjukkan sensitivitas sistem terhadap variabilitas daya dari energi angin dan tantangan dalam mengelola penurunan frekuensi akibat kehilangan PLTB. Respons sistem bervariasi pada periode beban puncak siang dan malam, dengan fluktuasi frek-uensi lebih kecil pada siang hari dibandingkan malam hari, kemungkinan disebabkan oleh perbedaan profil permintaan beban dan komposisi pembangkit. Temuan ini memberikan wawasan mengenai pengaruh PLTB terhadap kestabilan frek-uensi dan manajemen daya dalam sistem kelistrikan berbasis energi terbarukan.